Comparative Analysis of Error Sources in the Determination of Wear Volumes of Oscillating Ball-on-Plane Tests - Reichelt, Manuel; Cappella, Brunero (Frontiers in Mechanical Engineering, 2020)
The accurate determination of wear volumes is a prerequisite for the study of numerous tribological phenomena. Wear volumes can be measured with different techniques (profilometry, confocal microscopy, white light interferometry, atomic force microscopy) or else be calculated starting from some quantities (usually the width and the planimetric wear) measured from the wear scar. Advantages and drawbacks of the mentioned measuring techniques are shown by means of wear scars and calottes resulting from ball-on-plane tests with 100Cr6 specimens. When measuring wear volumes, white light interferometry results to be one of the most suitable techniques, since it offers high accuracy and is not as time consuming as atomic force microscopy. When wear volumes are calculated, errors result mainly from two sources: 1) the arbitrary choice of one or few line profiles for the determination of the width and of the planimetric wear, and 2) approximations in the calculation, which are even necessary when values of the wear volumes of the single tribological partners, i.e. ball and plane, and not only the total volume, are of interest. The effect of both the statistical distribution of values of the width and of the planimetric wear and the propagation of errors due to approximations on the accuracy in the determination of wear volumes is characterized and elucidated by examples. It is found that errors due to approximations are negligible when compared to errors due to the arbitrary choice of one line profile.